Abrigar... brincar: um estudo sobre as vivências lúdicas entre educadoras e crianças de um abrigo - Sousa, Anamaria Rodrigues Resende de (2006)
In light of the innumerous possibilities in playing that permit a child to interact with other children: discovering, establishing relations, finding solutions, creating and recreating reality among others, much research has been done with the intension to investigate how games occur in child institutions. Thus, the present study has the objective to understand the manner in which games are presented in a foster care institution located in the city of Uberlândia, Minas Gerais, Brazil. In addition, to evaluate how the educators use or don t use this resource in their interactions with the children. The research was delineated under the historical-cultural perspective represented by Vygotsky, which considers a game as a human social activity that creates a zone of proximal development. Eight foster children and seven educators, plus the coordinator of the foster care center participated in the study. The following methods were used: filmings of the game sessions, semi-structured interviews with educators and coordinator, reflexive interviews from the filmings, observations of the daily routines and available materials and toys, documented research and lab books. It was verified that the themes brought by the children refer to the representation of situations related to their daily ones in the institution, as well as situations lived in their family environment. It was observed that in make-believe situations the staff didn t explore the game to its fullest; in fact, they were a hindrance in the development of creative games. The reflexive interviews showed us an important instrument for the deepening of the theme researched likewise for the reflection about the experience on the part of the educator, especially regarding recreational activities. This study contributed to made clear the necessity of public politics to contemplate the quality of service in these institutions, furthermore, the urgency of training programs for professionals who work in this area.